Pengaruh Whistleblowing System, Sistem Pengendalian In-ternal, dan Budaya Organisasi Terhadap Pencegahan Fraud dalam Pengelolaan Dana Desa - Guntur Samudra; Tutut Dewi Astuti (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to investigate the prevention of fraud in village fund management in Muntuk Village, Bantul Regency, Yogyakarta, by analyzing the effects of organizational culture, internal control, and whistleblowing methods. The inquiry was initiated due to the increasing number of allegations of corruption involving village funds. These examples suggest that there is a lack of monitoring and integrity among the village leadership. Questionnaires were sent out to influential people in the community to collect data for this quantitative associative research. To analyze the data, multiple linear regression analysis was employed. The results show that whistleblowing procedures and corporate culture are more effective in preventing fraud than the internal control system. These findings highlight the critical need for better organizational culture and effective reporting methods to achieve transparent and accountable village governance.